Dividend Policy and Share Price Fluctuations of Sampled Quoted Nigerian Companies - Olaoye, Festus Oladipupo; Owoniya, Babajide Olumuyiwa (Archives of Business Research, 2017)
This focus of the study was to find out the impact of dividend policy on market price of shares on sampled quoted companies in Nigeria. Secondary data were sourced from the audited annual reports of ten selected companies, the prices from Central Security Clearing System‘s portal (CSCS) and annual returns on Nigeria Stock Exchange All Share Index-NSEASI from Proshareng.com for the period of 2011 to 2015. The data were analysed by the use of ols regression technique to find the level of significance of the variables: dividend payout ratio earnings per share and economy status on share price of sampled companies in Nigeria. The findings revealed that dividend payout ratio and earnings per share have significant effects on share price of equity while the economy status has insignificant effect on the share price of equity. The study also showed that earnings per share has a higher effect than dividend payout ratio and economy status of the country on market price of share of sampled companies in Nigeria during the period under review. It is recommended that in this recession period, risk averse investors should focus on high dividend payout ratio equities ,however they should be careful of these stocks because it means the companies may not have enough retained earnings to invest in profitable investments.